2021
DOI: 10.1101/2021.04.21.21255807
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A randomised clinical trial of azithromycin versus standard care in ambulatory COVID-19 – the ATOMIC2 trial

Abstract: BackgroundThe antibacterial, anti-inflammatory and antiviral properties of azithromycin suggest therapeutic potential against COVID-19. Randomised data in mild-moderate disease are lacking. We assessed whether azithromycin is effective in reducing hospitalisation in patients with mild-moderate COVID-19.MethodsThis open-label, randomised superiority clinical trial at 19 centres in the United Kingdom enrolled adults, ≥18 years, presenting to hospitals with clinically-diagnosed highly-probable or confirmed COVID-… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 30 publications
(23 reference statements)
0
5
0
Order By: Relevance
“…Four studies were identified using the search strategy, 7–9 and two additional studies were identified at a later stage using e‐mail alerts 36,37 . One additional trial, the ATOMIC2 trial, was included when it was published in April 2021 38 …”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Four studies were identified using the search strategy, 7–9 and two additional studies were identified at a later stage using e‐mail alerts 36,37 . One additional trial, the ATOMIC2 trial, was included when it was published in April 2021 38 …”
Section: Resultsmentioning
confidence: 99%
“…All studies reported the results based on pre‐specified protocols, and all were prospectively registered at one of the clinical trials registry platforms. Four trials were conducted in hospital settings, and three (Q‐PROTECT, ATOMIC2 and PRINCIPLE trials) were conducted in community settings 36–38 . Only two studies 39 , 40 included patients with severe Covid‐19.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations